Pergeseran Paradigma Sentralisasi ke Desentralisasi Dalam Mewujudkan Good Governance - Waris, Irwan (Universitas Riau, 2011)
Changing paradigms sentralized become decentralized, it is not easy. The problem is the conceptionof centralization has been understood by the people during the Dutch colonial era, the end of the Sukarnogovernment (Guided Democracy), and in the reign of Suharto (New Order). It is therefore not too surprisingthat the management of decentralization in the form of regional autonomy by using the concept of goodgovernance does not take place as expected. The application of this conception in the visible region was stillloaded with centralistic conception. The question is, should we give up? Should not give up, because somethingnew is to be learned while implemented. The thing to keep in mind is, in the learning phase should not be toolong and costly, especially at the expense of the people.